INFLUENCE OF DIFFERENT CATEGORIES OF FOLLICLES AND PRESENCE OF CL ON RECOVERY RATE, QUALITY AND QUANTITY OF BUFFALO OOCYTES - MAKWANA, P M; SHAH, R G; SINGH, R P; DHAMI, A J (The Indian Journal of Animal Reproduction, 2023)
The study was conducted on 408 freshly collected abattoir ovaries of Surti buffalo during peak breeding season. The total number of follicles recorded on these ovaries was 1369 and the overall mean number of follicles per ovary was found to be 3.36 ± 0.08. The mean number (percentage) of small, medium and large size follicles per ovary were 1.33 ± 0.05 (39.66), 1.32 ± 0.05 (39.44) and 0.70 ± 0.04 (20.89), respectively. Oocytes collected by slicing method were classified on the basis of cumulus investment and ooplasm homogeneity, viz., grade A (>3 layer of cumulus cells), grade B (1-3 layerof cumulus cells), grade C (less compact cumulus) and grade D (nude oocytes). The mean number of oocytes per ovary of grade A (0.82 ± 0.04) and B (0.79 ± 0.04) were significantly higher (P<0.05) than that of grade C (0.64 ± 0.04) oocytes. The small (<5 mm) follicles had highly significant (P<0.01) and positive correlations with grade A, B and C oocytes in decreasing order. Similarly, medium size follicles (5-8 mm) also had highly significant (P<0.01) and positive correlations with grade Band gradeAoocytes. Large follicles (>8 mm) showed significant (P<0.01) and positive correlations with grade D and grade C oocytes. Significantly (P<0.05) greater number of oocytes per ovary were recovered (3.77 ± 0.14) when CL was absent compared with its presence (2.70 ± 0.12). Further, significantly higher percentage (P<0.01) of recovery rate of grade A (27 %) and grade B (26.5 %) oocytes was obtained from the ovaries in which CL was absent than the ovaries in which CL was present (grade A: 22.40 % and grade B: 20.53 %). The effect of presence Vs absence of CL on the ovaries revealed 24 .53 Vs 20. 60 per cent recovery rate for grade C and 32.53 Vs 25.83 per cent for grade D oocytes. The study showed that functional structure on the ovaries, i.e. corpus luteum and size of follicles affect the recovery rate and quality of buffalo oocytes.